Optimalisasi Tingkat Pengguna Jalan yang Berkeselamatan untuk Mewujudkan Keamanan, Keselamatan, Ketertiban dan Kelancaran Lalu Lintas (Kamseltibcarlantas) T.A. 2021 - Azis Saputra (Pusat Penelitian dan Pengembangan Polri, 2022)
Transportation is one of the supports in lifes. both in rural and urban areas. Transportation can be divided into 3 types based on the area of ​​movement, such us land, sea and air transportation. Land transportation is the most dominant mode of transportation in Indonesia compared to sea and air transportation. Along with the development of trade, humans need more advanced transportation to carry goods efficiently. On the other hand, human mobility using land transportation has a high risk to the safety of body and soul and property. Traffic accidents will be directly proportional to the development of land transportation if they are not managed professionally and involve all stakeholders. During the period 2015 - 2019, the number of traffic accidents increased by average of 4.87% per year. The increase in the number of accidents was also followed by an increase in the number of fatalities and minor injuries, 1.41% and 6.2%. Traffic accidents in Indonesia by the World Health Organization (WHO) are considered to be the third biggest killer, after coronary heart disease and tuberculosis/TB. WHO records that 1.2 million people die each year in traffic accidents and 50 million victims of traffic accidents suffer serious or permanent injuries, generally those who die in traffic accidents are aged 15 to 44 years, and 77% are men. WHO, 2011). This research was conducted at 6 (six) Police regional in October 2021. This research used a qualitative approach by using interview guides and collecting secondary data. Respondents and informants are community leaders, religious leaders, youth leaders, Land Transport Organization, Religious Institutions, teachers, drivers, community observers of public transportation, the Department of Transportation, the Department of Public Works and Public Housing (PUPR), the Department of Education and Internal Traffic Functions (Head of Sub-Directorate. The results of the study state that: 1) This survey shows that the attitudes, perceptions and knowledge of the community support the road safety program. 2) Dominant factors that affect traffic accidents can be caused by human factors, vehicles that do not comply with specifications and dimensions, transportation infrastructure that is not in accordance with the structure and function of roads and environmental factors where livestock roam the roads, smoke from forest and land fires, mass concentration in certain areas; 3) The level of traffic violations and accidents is dominated by drivers with SIM C 45.6%. Where violations by type of two-wheeled vehicles are 82% and motorcycle riders also dominate traffic accidents by 75%; 4) Traffic violations by drivers who do not have a driving license are quite high at 35.3%; 5) Traffic violations by age category are dominated by the age of 17-25 years (millennials) at 36%, the age category is according to the category of profession/work as a student/student of 25.9%. Perpetrators of accidents for the category of students / students by 30.6%; 6) Traffic accidents often occur in the time range 15.00-17.59 (afternoon) with 593 incidents, in the time range from 21.00-23.59 (night) with 536 incidents and in the time range 12.00-14.59 (days) with 525 incidents; 7) Based on road status, accidents are dominated by 33% on National roads and 32% on Provincial roads. The efforts of the National Police in realizing Kamseltibcarlantas for road users in the context of creating Kamseltibcarlantas, the ranks of traffic functions have carried out educational activities, traffic engineering, and law enforcement. Educational activities for groups of children and adolescents as well as transportation observer communities, but the impact on community traffic discipline is still lacking because so far no evaluation has been carried out. In an effort to anticipate areas prone to congestion and traffic accidents, the ranks of the traffic function have carried out a number of traffic engineering by installing traffic signs, diverting/closing traffic flows. by involving relevant agencies. Keyword: Accident, Violation, Road safety, Road users